Limited commitment models of the labor market - Jonathan P. Thomas; Tim Worrall (Center for Economic Studies and ifo Institute (CESifo), 2007)
We present an overview of models of long-term self-enforcing labor contracts in which risk sharing is the dominant motive for contractual solutions. A base model is developed which is sufficiently general to encompass the two-agent problem central to most of the literature, including variable hours. We consider two-sided limited commitment and look at its implications for aggregate labor market variables. We consider the implications for empirical testing and the available empirical evidence. We also consider the one-sided limited commitment problem for which there exists a considerable amount of empirical support.
Keywords: E32; J41; 330; Arbeitsvertrag; Theorie